Morphological characterization of Indian mustard (Brassica juncea) genotypes and their application for DUS testing - YADAV, ASHOK KUMAR; SINGH, DHIRAJ; ARYA, RAJESH KUMAR (The Indian Journal of Agricultural Sciences, 2026)
Present study on morphological characterization of Indian mustard (Brassica juncea (L.) Czern and Coss) genotypes/ varieties developed by CCS Haryana Agricultural University, Hisar was carried out and established distinctness among different genotypes under study. A total of 78 genotypes were grouped for several morphological descriptors. The number of lobes varies from low to medium. Stem colour varies from light green to dark green. Wide diversity has been observed for leaf length (40.2 to 63cm) and leaf breadth (18 to 27cm) also. No variability was observed for leaf division, petiole enlargement, petiole section, petiole colour, flower colour and silique surface outline. In majority of cases, it was observed that leaf angle was prostrate type, leaf blade shape was spathulate, leaf division dentate lyrate type, leaf apex and leaf blistering was intermediate, leaf tip and lamina attitude was straight, sparse hairs were present. Petiole length, width and thickness were intermediate type. Similar, findings were also observed for petal length, breadth, silique angle, length and width and also for pedicel and beak length. Seed colour of all the genotype was black colour except RH 401Y which was yellow in colour. Maximum genotype were of medium size (3-5g/1000 seed weight) except RH 270 (bold seed>5g/1000 seed weight). The characterization of released/pre-released genotype/varieties will provide valuable information for strengthening of future breeding programme on Indian mustard. All the 78 genotypes/ varieties are grouped into different categories on the basis of present characterization for each character and may be used as reference genotypes/varieties. Further, this characterization could be utilized for maintaining the genetic purity of a genotype as well as DUS testing becomes easy in a well characterized genotype.